2021
DOI: 10.1155/2021/9877205
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Vascular Response to Hyperoxia in Patients with Diabetes Mellitus without Diabetic Retinopathy

Abstract: Purpose. To evaluate the retinal vascular response to hyperoxia in patients with diabetes at the preclinical stage of diabetic retinopathy (DR) and to quantify the changes in comparison with normal subjects using optical coherence tomography angiography (OCTA). Methods. In this prospective study, 40 eyes of 20 participants comprising 10 diabetic patients with no diabetic retinopathy (NDR) and 10 normal subjects were recruited. OCTA images were acquired in the resting position and were repeated after a hyperoxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 34 publications
(41 reference statements)
0
3
1
Order By: Relevance
“…The increase in foveal SCP VD failed to reach the signi cance level (P = 0.059) which could be attributed to small sample size. In a study evaluating retinal vascular response to hyperoxia, normal individuals showed a reduction in parafoveal DCP VD due to autoregulatory mechanisms, however, in diabetic patients without retinopathy such a reduction was not observed [30]. Impaired autoregulation might have a role in the increased VD observed in patients with DMI in our study which ultimately might be bene cial in these patients.…”
Section: Discussioncontrasting
confidence: 55%
See 2 more Smart Citations
“…The increase in foveal SCP VD failed to reach the signi cance level (P = 0.059) which could be attributed to small sample size. In a study evaluating retinal vascular response to hyperoxia, normal individuals showed a reduction in parafoveal DCP VD due to autoregulatory mechanisms, however, in diabetic patients without retinopathy such a reduction was not observed [30]. Impaired autoregulation might have a role in the increased VD observed in patients with DMI in our study which ultimately might be bene cial in these patients.…”
Section: Discussioncontrasting
confidence: 55%
“…Several studies have shown the effects of supplemental oxygen on retinal function or structure in diabetic patients with [10-12, 31, 32] or without retinopathy [30] and other retinal ischemic conditions [19,33] or retinal vascular occlusions [34][35][36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have proved that compared with normal people, the vessel density of SCP and DCP in the early stage of DR will decrease, reflecting the vascular injury in the early stage of DR, and with the progress of DR, a large range of nonperfusion areas may eventually appear in the retina. 32 At the same time, compared with SCP, DCP and DVP can better reflect the vascular changes of DR, and the injury time is longer, which makes some non-perfusion areas irreversible. [33][34][35] There were no statistical differences for SVP, ICP and DCP of the three groups in this study, probably because patients who have developed PDR requiring surgery have irreversible damage to the fundus microvascular circulation and injectable drugs do not improve retinal microcirculation in the short term.…”
Section: Discussionmentioning
confidence: 99%
“…Safi et al assessed the retinal vascular response to hyperoxia in patients with diabetes at the pre-clinical stage of DR and compared it with normal controls. They found that impaired retinal vascular reactivity was apparent at this stage, with disturbances in the autoregulatory mechanism particularly pronounced in the parafoveal DCP [121]. This finding further underscored that the DCP experiences more severe microvascular damage than the SCP in patients with DM or DR at the early stage [122].…”
Section: Retinal Vessel Reactivitymentioning
confidence: 94%